2016
DOI: 10.1126/scitranslmed.aad3099
|View full text |Cite|
|
Sign up to set email alerts
|

The caspase-8 inhibitor emricasan combines with the SMAC mimetic birinapant to induce necroptosis and treat acute myeloid leukemia

Abstract: Resistance to chemotherapy is a major problem in cancer treatment, and it is frequently associated with failure of tumor cells to undergo apoptosis. Birinapant, a clinical SMAC mimetic, had been designed to mimic the interaction between inhibitor of apoptosis proteins (IAPs) and SMAC/Diablo, thereby relieving IAP-mediated caspase inhibition and promoting apoptosis of cancer cells. We show that acute myeloid leukemia (AML) cells are sensitive to birinapant-induced death and that the clinical caspase inhibitor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(153 citation statements)
references
References 46 publications
8
145
0
Order By: Relevance
“…HT29 cells treated with IFNγ/SM also upregulated caspase-10, and various cleaved forms were detected (Figure 6a). Addition of the pancaspase inhibitor IDN-6556, a more potent caspase inhibitor than QVD, 49 prevented the formation of the smallest processed product of caspase-10 (p25), which served as the clearest signature of caspase-10 activation (Figure 6a). As expected, IFNγ/SM/IDN-6556 treatment also induced MLKL phosphorylation (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…HT29 cells treated with IFNγ/SM also upregulated caspase-10, and various cleaved forms were detected (Figure 6a). Addition of the pancaspase inhibitor IDN-6556, a more potent caspase inhibitor than QVD, 49 prevented the formation of the smallest processed product of caspase-10 (p25), which served as the clearest signature of caspase-10 activation (Figure 6a). As expected, IFNγ/SM/IDN-6556 treatment also induced MLKL phosphorylation (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, there is little to suggest that oncogenic transformation per se renders cells significantly more sensitive to RIPK1/RIPK3 responses in a cell autonomous manner. On the other hand, data using combination of SMAC mimetics or TLR3 agonist poly(I:C) in combination with pan-caspase inhibitors suggest that such necroptosis-inducing stimuli may be well tolerated and efficacious (66,80). One possibility is that only a very limited degree of RIPK1/RIPK3 cell death may be needed to get the immune system fired up to target the cancer, as some of the positive responses were not observed in immune-deficient animals (35, 80).…”
Section: Discussionmentioning
confidence: 99%
“…Finding conditions to drive necroptosis activation by these molecules emerged as one productive approach to achieve excellent anti-tumor activity. As mentioned above, Brumatti et al (66) showed that combining birinapant with pan-caspase inhibitor IDN6556 resulted in greatly increased efficiency of cell death.This combination induced necroptosis, compared to apoptosis induced by birinapant alone, and was effective even in the cells specifically selected in vitro to be resistant to birinapant. This also translated into birinapant+IDN combination causing improved tumor regression and survival of animals transplanted with MLL-ENL murine leukemia cells.…”
Section: As D I S C U S S E D a B O V E A C T I V A T I O N O F R Imentioning
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with independent studies showing that deletion of Ripk3 did not alter disease progression of MLL-ENL-, MLL-AF9-, NUP98-HoxA9-, and HoxA9/Meis1-induced leukemia. 6,7 Furthermore, the authors showed that these leukemia subsets were sensitive to killing by the SMAC mimetic birinapant in a RIPK1/TNFR1-dependent manner. Therefore, our work suggests that alternative therapeutic approaches will be required for AML subsets with reduced RIPK3 expression.…”
mentioning
confidence: 99%